(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This study will analyze the marketing strategies andtactics that will be generally adopted by marketers during time of recession.The signs of recession usually decrease consumer confidence and the consumerspending in products and services. But for a marketer Recession is consideredopportunity as well as difficult phase. Period of opportunity because it is the time to take an objective lookat their brand portfolio and to analyze which brand in the portfolio offersmore value to the consumer and difficult time in the sense that due to decreasein spending power of customer, marketing the product becomes difficult. A majorstep here becomes know the consumer- Know what they think and know where theyare and how these economic times are hitting them. So marketing becomes achallenge for a marketer during time of Recession